A Randomized Controlled Trial Evaluating the Efficacy of Perioperative Acupuncture Combined with Traditional Chinese Medicine for Enhancing Upper Limb Functionality after Breast Cancer Surgery - PATIGULI Jiapaer; JIANG Ke; YUAN Minjia; LI Xiaofei; DONG Mengting; SHENG Jiayu (康复学报, 2025)
ObjectiveTo explore the effect of oral Qi-Zhu Formula combined with electroacupuncture on postoperative pain and upper limb dysfunction in patients with breast cancer during the perioperative period.MethodsA total of 90 patients who underwent radical mastectomy in the department of breast diseases of Yueyang Hospital of Integrated Traditional Chinese and Western Medicine affiliated to Shanghai University of Traditional Chinese Medicine between January 2022 and December 2022 were randomly assigned to either a conventional medicine group or a combined electroacupuncture and medicine group, with 45 cases in each group. Both groups received standard postoperative treatment and took the traditional Chinese medicine Qi-Zhu Formula orally. The conventional medicine group received sham electroacupuncture treatment, while the combined electroacupuncture and medicine group received electroacupuncture treatment. Pain levels were assessed before and after treatment using the Short Form McGill Pain Questionnaire (SF-MPQ) in the two groups; Upper limb functions were evaluated by shoulder joint range of motion (ROM), quick disabilities of the arm, Shoulder and Hand (DASH) questionnaire, and grip strength measurement. Quality of life was compared between the two groups using the Functional Assessment of Cancer Therapy-Breast (FACT-B) scale.ResultsCompared with that before treatment, the PRI score, VAS score and PPI index of SF-MPQ scale in the two groups significantly decreased after treatment (P<0.05). Compared with the conventional medicine group, the PRI score, VAS score and PPI index were significantly lower in the combined electroacupuncture and medicine group (P<0.05). At one month post-surgery, compared with the conventional medicine group, the abduction, flexion, and extension ROM in the shoulder joint were significantly higher in the combined electroacupuncture and medicine group (P<0.05). At three months post-surgery, compared with the conventional medicine group, the abduction and flexion ROM were significantly higher in the combined electroacupuncture and medicine group (P<0.05). At six month post-surgery, compared with the conventional medcine group, the abduction ROM were significantly higher in the combined electroacupuncture and medicine group (P<0.05). At one month post-surgery, in the comparison of abduction, flexion and extension activities, the abduction ROM in the combined electroacupuncture and medicine group accounted for the highest proportion of the expected value in the two groups, reaching 75.17% (P<0.05); at three and six months post-surgery, the proportion of different joints ROM in the expected value of the two groups increased compared with that before surgery (P>0.05). At one and three months post-surgery, compared with the conventional medicine group, the DASH scores were lower in the the combined electroacupuncture and medicine group (P<0.05). Compared with one month post-surgery, the DASH scores were lower in both groups at three and six months post-surgery (P<0.05).At one and three months post-surgery, compared with the conventional medicine group, the grip strength was higher in the combined electroacupuncture and medicine group (P<0.05). Compared with one month post-surgery, the grip strength was higher in both groups at three and six months post-surgery (P<0.05). At one month post-surgery, compared with the conventional medicine group, the scores of physiological status, functional status and additional concern domain in FACT-B were significantly higher in the combined electroacupuncture and medcine group.ConclusionFor patients with breast cancer, routine oral administration of Qi-Zhu Formula combined with perioperative electroacupuncture can reduce postoperative pain, improve shoulder ROM early, improve limb dysfunction, and effectively promote early postoperative rehabilitation.